International sports organizations: FIFA and the IOC seen through political geography - Celis Galindo, Dante Guillermo; Montes Vega, Octavio Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The International Federation of Association Football (FIFA) and the International Olympic Committee (IOC) are two international sports organizations with an instrumental functioning within large international corporations. They also have influence in national states through the generation of ecological discourses and investment funds in public works, which leads them to be a key player in the production of capital spaces. Sports companies have become a fundamental actor in understanding the mechanisms of social and cultural alienation for many members of the working class, but this would not be understandable without international sports organizations that function as intermediaries between companies and the consumer population. Political geography, in its critical aspect, is crucial for the analysis of this process of production of the space that generates this process of intermediation between sports companies, institutional organizations and consumers of professional sports.For this, an inductive methodology was carried out, since the work arises from an investigation into the role of international organizations in the countries organizing mega sporting events.